DAMPAK NARSISME PEMIMPIN TERHTERDAPATP KINERJA ORGANISASI: TINJAUAN LITERATUR MULTILEVEL PADA TINGKAT INDIVIDU, TIM, DAN ORGANISASI - Yuanus, Franki; Choirunnisa, Zuyyinna; Putra, Yudistira Ardi Nugraha Setyawan (Universitas Djuanda, 2025)
Leader narcissism is a multifaceted personality construct characterized by grandiosity and a need for admiration, which may interact with other traits within the